Analysis of the role of geranylgeranyl diphosphate synthase 8 from Tripterygium wilfordii in diterpenoids biosynthesis. (August 2019) - Su, Ping; Gao, Linhui; Tong, Yuru; Guan, Hongyu; Liu, Shuang; Zhang, Yifeng; Zhao, Yujun; Wang, Jiadian; Hu, Tianyuan; Tu, Lichan; Zhou, Jiawei; Ma, Baowei; et al.
Highlights: GGPPS1, GGPPS7 and GGPPS8 catalyzed the successive addition of IPP to DMAPP, GPP and FPP to form GGPP. GPPS.SSU was inactive alone but interacted with GGPPS1, GGPPS7 and GGPPS8 to change the product from GGPP to GPP. GGPPS8 exhibited the highest catalytic efficiency to catalyze the formation of GGPP among the three functional GGPPSs. GGPPS8 showed the similar transcript level with that of the terpene synthase genes involved in triptolide biosynthesis. GGPPS8 was most likely to participate in triptolide biosynthesis in roots. Abstract: Tripterygium wilfordii is known to contain various types of bioactive diterpenoids that exhibit many remarkable activities. Many studies have recently been targeted toward the elucidation of the diterpenoids biosynthetic pathways in attempts to obtain these compounds with a view to solving the dilemma of low yield in plants. However, the short-chain prenyltransferases (SC-PTSs) responsible for the formation of geranylgeranyl diphosphate (GGPP), a crucial precursor for synthesizing the skeleton structures of diterpenoids, have not been characterized in depth. Here, T. wilfordii transcriptome data were used to identify eight putative GGPPSs, including two small subunits of geranyl diphosphate synthase (GPPS.SSU). Of them, GGPPS1, GGPPS7, GGPPS8, GPPS.SSU II and GPPS.SSU were translocated mainly into chloroplasts, and GGPPS8 exhibited the optimal catalytic efficiency with respect to catalyzing the formation of GGPP. In addition, the expression pattern of GGPPS8 was similar to that of downstream terpene synthase genes that are directly correlated with triptolide production in roots, indicating that GGPPS8 was most likely to participate in triptolide biosynthesis in roots among the studied enzymes. GPPS.SSU was inactive alone but interacted with GGPPS1, GGPPS7 and GGPPS8 to change the product from GGPP to GPP. These findings implicate that these candidate genes can be regulated to shift the metabolic flux toward diterpenoid formation, increasing the yields of bioactive diterpenoids in plants.